Intracranial Aneurysms: Does Size Really Matter?. Issue 4 (30th November 2020) - Majeed, Kashif; Boddu, Srikanth R; Carnevale, Joseph; Cenberlitas, Elif Ezgi; Williams, Nicholas; Patsalides, Athos; Gobin, Yves Pierre; Knopman, Jared; Stieg, Philip E
Abstract: BACKGROUND: To stratify the risk of aneurysmal rupture, size remains the primary criterion as proposed by 2 ISUIA (International Study of Unruptured Intracranial Aneurysms) trials that recommend the observation of ≤7 mm aneurysms because of their low propensity to rupture. These recommendations are controversial, given the severe outcomes following hemorrhage. OBJECTIVE: To retrospectively assess whether size correlates with aneurysmal rupture, and to analyze outcomes of endovascular and microsurgical procedures. METHODS: All aneurysms presenting between 2016 and 2019 were reviewed. Age, gender, comorbidities, ruptured status, modes of treatment, and their outcomes were noted. Regression analysis was performed to correlate size with rupture. The type of intervention was based on clinical and aneurysmal characteristics and the likelihood of obliteration. RESULTS: Of the 668 aneurysms, 116 had ruptured. In size groups 0 to 6 mm,  7 to 12 mm,  13 to 18 mm,  18 to 24 mm,  and giant, the ruptured aneurysms were 60.3%, 30.2%, 1.7%, 0.9%, and 6.9%, respectively. The majority (423) were managed endovascularly, of which 84 (19.9%) were ruptured. A total of 97 (14.5%) underwent clipping, of which 31 were ruptured. The mean modified Rankin Scale for both treated groups was zero. One death in each group and a single brainstem stroke in the coiled group were noted. A total of 139 were followed, of which none had ruptured. The mean modified Raymond-Roy classification for endovascular therapy was 1.1, with 380 completely occluded; 15 had a score of 2, and 28 of score 3. CONCLUSION: The ruptured aneurysms were mostly smaller than reported previously. Surgical clipping was at equipoise with endovascular treatments. Further studies to correlate aneurysmal characteristics to the risk of rupture are needed.